Optimization Process of Virgin Coconut Oil Production to Meet The Quality of Lulur Cosmetics (Biopropal Industri, 2010)
Optimization process of virgin coconut oil (VCO) production to meet the  quality of lulur cosmetics was carried out in the Institute for Industrial Research and Standardization Pontianak. This research aimed to  increase the productivity of pure coconut oil both quantity nor quality that were produced so it can meet the quality characteristics as  raw material of  lulur cosmetic. This research was use coconut and pineapple in a local species as the main raw material and other supporting materials such as VCO and others. There were 2 (two) treatment factor used  namely  A (bromelin extract volume) and B (mixing time). The parameters observed were water content, acid number, saponification  number, and free fatty acid (FFA). Results showed that the treatment without bromelin extract  with 5 minutes mixing time were the best treatment for raw material of lulur cosmetic, with the  water content 0.122%, the free fatty acid 0.062%, the acid number 0.174, and saponification  number 261,21  (the condition for oil as the cosmetic raw material was 0.2% max.).